Kajian Terhadap Perikatan Alamiah Menurut Kitab Undang–Undang Hukum Perdata (KUH Perdata) - bing waluyo (Wijayakusuma Law Review, 2021)
Abstract The source of the engagement as regulated in Article 1233 of the Civil Code, can occur due to two things, namely an engagement born of an agreement and an engagement born of law. Engagements born from laws consist of engagements born from laws only and those born from laws due to human actions which can be distinguished into human actions that are in accordance with the law (rechtmatige) and those that are against the law (onrechtmatige). Engagements born from the law due to human actions in accordance with the law, one of which is contained in Article 1359 of the Civil Code, which consists of two paragraphs, namely paragraph 1 which regulates the right to claim back payments that are not owed, and paragraph 2 regulates if a person legally voluntarily fulfill the obligations of the natural engagement, then the payment is not a payment that is not owed, it can be concluded from the contents of the article, namely that the payment made by the debtor cannot be requested back. Furthermore, regarding how and what is meant by natural engagement, the Civil Code does not explain in detail, on this basis it encourages the author to write a study on natural engagement according to the Civil Code (KUH Perdata). The approach method in this paper is normative juridical, while the specifications in this paper are descriptive analytical. Keywords: Study, Engagement, Natural Engagement, Civil Code. Sumber perikatan yang diatur dalam Pasal 1233 KUH Perdata, dapat terjadi karena dua hal, yaitu perikatan yang dilahirkan dari suatu perjanjian dan perikatan yang dilahirkan karena undang-undang. Perikatan yang lahir dari undang-undang terdiri dari perikatan-perikatan yang lahir dari undang-undang saja dan yang lahir dari undang-undang karena perbuatan manusia yang dapat dibedakan menjadi perbuatan manusia yang sesuai dengan hukum (rechtmatige) dan yang bersifat melawan hukum (onrechtmatige). Perikatan yang lahir dari undang-undang karena perbuatan manusia yang sesuai dengan hukum, salah satunya terdapat dalam Pasal 1359 KUH Perdata, yang terdiri dari dua ayat yaitu ayat 1 mengatur hak untuk menuntut kembali pembayaran yang tidak terhutang, dan ayat 2 nya mengatur apabila seseorang secara sukarela memenuhi kewajiban perikatan alamiah, maka pembayaran itu bukan merupakan pembayaran yang tak terhutang, hal ini dapat disimpulkan dari isi pasal tersebut yaitu bahwa pembayaran yang telah dilakukan oleh debitur tidak dapat diminta kembali. Selanjutnya tentang bagaimana dan apa yang dimaksud dengan perikatan alamiah, KUH Perdata tidak menjelaskan secara rinci, atas dasar inilah mendorong penulis untuk menulis kajian terhadap perikatan alamiah menurut Kitab Undang-Undang Hukum Perdata (KUH Perdata). Adapun metode pendekatan dalam penulisan ini adalah yuridis normatif, sedang spesifikasi dalam penulisan ini adalah deskriptif analistis. Kata Kunci : Kajian, Perikatan, Perikatan Alamiah, KUH Perdata